The widows of malabar hill ebook - Massey, Sujata (Perveen Mistry,, 2018)
1920s India: Perveen Mistry, Bombay's only female lawyer, is investigating a suspicious will on behalf of three Muslim widows living in full purdah when the case takes a turn toward the murderous. The author of the Agatha and Macavity Award–winning Rei Shimura novels brings us an atmospheric new historical mystery with a captivating heroine. This Deluxe Edition features: an interview with the author, discussion questions, essays on the real-life inspirations behind the novel, delicious recipes taken from the story, and previews of The Satapur Moonstone (May 2019). Perveen Mistry, the daughter of a respected Zoroastrian family, has just joined her father's law firm, becoming one of the first female lawyers in India. Armed with a legal education from Oxford, Perveen also has a tragic personal history that makes women's legal rights especially important to her. Mistry Law has been appointed to execute the will of Mr. Omar Farid, a wealthy Muslim mill owner who has left three widows behind. But as Perveen examines the paperwork, she notices something strange: all three of the wives have signed over their full inheritance to a charity. What will they live on? Perveen is suspicious, especially since one of the widows has signed her form with an X—meaning she probably couldn't even read the document. The Farid widows live in full purdah—in strict seclusion, never leaving the women's quarters or speaking to any men. Are they being taken advantage of by an unscrupulous guardian? Perveen tries to investigate, and realizes her instincts were correct when tensions escalate to murder. Now it is her responsibility to figure out what really happened on Malabar Hill, and to ensure that no innocent women or children are in further danger. Inspired in part by the woman who made history as India's first female attorney, The Widows of Malabar Hill is a richly wrought story of multicultural 1920s Bombay as well as the debut of a sharp new sleuth.